Factores de riesgo que influyen en la contaminación del catéter venoso central en la unidad de cuidados intensivos - Pavón Ávila, Jhoana Ibeth (2025)
Background: Central venous catheter (CVC)-related infections are a common problem in intensive care units (ICUs) and are associated with increased morbidity and mortality. These infections are largely due to failures in aseptic manipulation techniques. Objective: To determine the risk factors influencing the contamination of central venous catheters in patients in the intensive care unit. Methods: A mixed-methods study with quantitative and qualitative elements, conducted in an ICU with the participation of 18 nursing professionals. A structured survey was used to collect data on aseptic practices and the frequency of preventive measures such as hand washing and the use of sterile gloves. Results: 100% of the staff perform hand washing before manipulating the CVC, but only 55.6% always use sterile gloves. The main cause of contamination identified was the lack of aseptic technique, reported by 66.6% of respondents. Conclusions: It is necessary to implement continuous training programs to ensure the correct use of aseptic techniques during CVC manipulation and reduce the risk of infections.